2021
DOI: 10.1007/s11192-021-04110-x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the relative intensity of collaboration within a network

Abstract: In research fields like informetrics or patent research, international comparisons are part of their core business. One class of measures used in such comparisons consists of affinity indices. Here, relations of shares are calculated to express the relation between two actors X and Y. Even though this group of affinity indices already has many members, we think that based on pure logic, they still miss the point. For this reason, we introduce the RIC index. This index compares two shares: the share of actor Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Assuming that country X in Eq. ( 2 ), from Fuchs et al ( 2021 ) is now the target country L and country Y is now L j (the j th country), then C X,Y is now denoted as s j ; C X is now denoted as ; C Y being the total number of collaborations country Y has with all other countries except country X , is here denoted as r j and T – C X , the total number of pairwise country collaborations, not including those with country X , in the set of studied publications is now . Consequently, and .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that country X in Eq. ( 2 ), from Fuchs et al ( 2021 ) is now the target country L and country Y is now L j (the j th country), then C X,Y is now denoted as s j ; C X is now denoted as ; C Y being the total number of collaborations country Y has with all other countries except country X , is here denoted as r j and T – C X , the total number of pairwise country collaborations, not including those with country X , in the set of studied publications is now . Consequently, and .…”
Section: Methodsmentioning
confidence: 99%
“…In Fuchs et al ( 2021 ), we recently reviewed the literature on collaboration indicators and found reason to modify an often-used indicator that was first introduced in the article entitled “Understanding patterns of international scientific collaboration” by Luukkonen et al ( 1992 ). In this article, the authors define the relative importance of country Y for country X as: …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vi bruker et dobbelt kriterium for viktighet. Det ene er relativ samarbeidsintensitet (Relative Intensity of Collaboration, RIC, utviklet av Fuchs et al, 2021), en indikator som sammenligner aktiviteten i en bilateral relasjon med all annen aktivitet i en matrise av globale samarbeidsrelasjoner. Indikatoren viser hvordan et land prioriterer samarbeidet uavhengig av landenes størrelse.…”
Section: Forsvarsallianser Og Forskningssamarbeidunclassified
“…Early examples include Frame & Carpenter (1979) and later studies have confirmed the trends towards increased international collaboration and networks in science (see e.g., Adams 2012;2013). Studies of international collaboration have also moved forward with conceptual clarifications (e.g., Katz & Martin, 1997), new indicators, e.g., of collaboration intensity (Coccia, & Bozeman 2016;Fuchs et al, 2021;Luukkonen et al, 1992), new visualization technologies (e.g., Van Eck & Waltman, 2014) and utilizing additional databases such as Scopus (Fu et al 2022) Also, international collaboration (or collaboration more generally) has been addressed from a citation impact perspective, showing that such papers tend to be cited more than other articles (see e.g., Thelwall et al 2023a).…”
Section: Introductionmentioning
confidence: 98%